2020
DOI: 10.1128/aac.01884-19
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled, Respiratory Syncytial Virus Human Challenge Study of the Antiviral Efficacy, Safety, and Pharmacokinetics of RV521, an Inhibitor of the RSV-F Protein

Abstract: Effective treatments for respiratory syncytial virus (RSV) infection are lacking. Here, we report a human proof-of-concept study for RV521, a small-molecule antiviral inhibitor of the RSV-F protein. In this randomized, double-blind, placebo-controlled trial, healthy adults were challenged with RSV-A Memphis-37b. After infection was confirmed (or 5 days after challenge virus inoculation), subjects received RV521 (350 mg or 200 mg) or placebo orally every 12 h for 5 days. The primary endpoint was area under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 24 publications
(40 reference statements)
2
46
0
Order By: Relevance
“…Primary efficacy end point of the model was typically shed virus load in nasal swab samples, secondary end points included total mucus weight produced during the acute infection period and symptom scores. Currently available trial outcome data show that three of the entry inhibitor candidates tested, presatovir (GS-5806) [94], RV521 [95], and JNJ-53718678 [96], reduced viral burden, shortened disease duration, and/or alleviated secondary clinical signs.…”
Section: Clinical Efficacy Of Small Molecule F Protein Inhibitorsmentioning
confidence: 99%
“…Primary efficacy end point of the model was typically shed virus load in nasal swab samples, secondary end points included total mucus weight produced during the acute infection period and symptom scores. Currently available trial outcome data show that three of the entry inhibitor candidates tested, presatovir (GS-5806) [94], RV521 [95], and JNJ-53718678 [96], reduced viral burden, shortened disease duration, and/or alleviated secondary clinical signs.…”
Section: Clinical Efficacy Of Small Molecule F Protein Inhibitorsmentioning
confidence: 99%
“…Meaningful human- and donor-specific data can be captured through emergent culture systems in lieu of challenge experiments, which are hindered by the severity of the agent being tested and participant acquisition [ 103 , 104 ]. For example, work by Peretz et al showed that cultures responded to sex hormones according to the sex of the primary cell donor.…”
Section: Application Of In Vitro Airway Models With Emergent Propementioning
confidence: 99%
“…In conclusion, a safe and reproducible human experimental model of RSV infection and disease was developed, and the developmental process may parallel potential COVID‐19 HVCM development in several ways. The RSV HVCM has already proven its worth in quickly establishing important human therapeutic efficacy and in speeding the development of experimental interventions which are now being conducted in high‐risk populations 45 . Additionally, the RSV HVCM has provided the first evidence of RSV vaccine efficacy in producing sterilising immunity and disease severity reductions 46 …”
Section: Preliminary Clinical Assessment Of Challenge Agentmentioning
confidence: 99%